Analysis of Movie I Am Not Stupid 2: Parenting Style 分析《小孩不笨2》电影的父母教育法 - Mariana Mariana (Bina Nusantara University, 2015)
This paper, through Singaporean movie I am not Stupid 2, analyzes the relation between parenting and children’s growth process and also the action of parents should do to offer children for having a good growth process. Research was done based on Baumrind theory about parenting analysis to what kind of parenting that the parents of the movie I am not Stupid 2 offer to their children. Research used literature study to summarize, arrange, and analyze of Diana Baumrind as basis of the research. The results show that Tom and Jerry’s parents or Cheng Cai’s father used authoritarian parenting style. Research suggests that the best parenting style is authoritative parenting because this type of parenting does not only concern about the prominence of rules or regulations in the family, but also the affection of parents towards the children. Therefore, the family will certainly become more harmonious.